Efficacy of recombinant Newcastle disease virus, RAF-IL12 as a potential therapeutic cancer vaccine in CT26 and HT29 cancer cell line and in mouse model - Syed Najmuddin, Syed Umar Faruq (2019)
Colon cancer remains one of the main cancer-causing death in men and women worldwide given that certain colon cancer subtypes are resistant to the conventional treatments and the development of new cancer therapy remains elusive. Alternative modalities such as the use of viral-based therapeutic cancer vaccine is still limited as only herpes simplex virus (HSV) expressing granulocyte-macrophage colony- stimulating factor (GM-CSF) or talimogene laherparepvec (T-Vec) had been approved in the USA and Europe. Therefore, it is imperative to continue the search for a new treatment modality such as the use of combinatorial therapy between the oncolytic Newcastle disease virus (NDV) and interleukin-12 (IL-12) cytokine as a potential therapeutic vaccine to the current anti-cancer drugs available in the market. Moreover, this combination between NDV and IL-12 against colon cancer is yet to be discovered and would probably lead to much better outcomes compared to their individual treatments. NDV is a paramyxovirus which infects and causes severe respiratory and central nervous disease in poultry and avian species leading to mortality, but it could also target and kill cancer cells. In light of the previous success of the wild-type NDV utilized against several cancer cell types, this project aims to study the anti-cancer effects of recombinant NDV, AF2240-i strain expressing IL-12 (rAF-IL12) in CT26 and HT29 colon cancer cells, which could potentially provide a better outcome in comparison to the wild-type strain, AF2240-i (i.e. used as a positive control in the in vitro and in vivo assays). In this study, rAF-IL12 was hypothesized to induce apoptosis in CT26 and HT29 in vitro and in vivo, modulate immune response in tumor-burden mice, and have no effects towards normal cells and tissues. MTT anti-proliferative assay revealed that the IC50 value of rAF-IL12 against CT26 and HT29 cell lines was 276 HA unit and 110 HA unit, respectively. These IC50 values were used as treatment dosage in the other in vitro assays such as AO/PI, Annexin V FITC, and cell cycle analysis. The rAF-IL12 treatment showed significant (p<0.05) cytotoxicity effects towards CT26 and HT29 cancer cells when compared to the AF2240-i as revealed by the MTT, AO/PI, and Annexin V FITC assay. Meanwhile, in the cell cycle analysis, the rAF-IL12 significantly (p<0.05) induced cell cycle arrest at G1 phase in CT26 cells and significantly (p<0.05) caused apoptosis at G0 phase in HT29 cells. Following the convincing results in vitro, further evaluation of rAF-IL12 against colon cancer were carried out in vivo by inducing the CT26 and HT29 cells in Balb/c and NCr Foxn1 nude mice, respectively. Treatment with rAF-IL-12 (dosage= 128 HA unit) significantly (p<0.05) decreased the weight and volume of tumor in both CT26 and HT29 tumor-bearing mice in comparison to the untreated and parental NDV, AF2240-i groups. Treatment with rAF-IL12 had also significantly (p<0.05) increased the number of apoptotic cells when compared to the other groups as revealed by TUNEL assay. Additionally, rAF-IL12 was also shown to significantly (p<0.05) modulate immune system by elevating the level of CD4+ and CD8+ T-cells as well as interleukin-2, interleukin-12, and interferon-gamma. In addition, rAF-IL12 could significantly (p<0.05) modulate the expression level of several genes in the CT26 (KRAS, BRAF, MAPK1, NOTCH-1, BAX, p53, CCL2, and VEGF-A) and HT29 (Fas, caspase-8, BID, BAX, SMAD3, and granzyme B) tumor-bearing mice. Furthermore, the immunohistochemistry analysis of HT29 tumors revealed the anti-metastatic and anti-angiogenic potential of rAF-IL12 as it could significantly (p<0.05) decrease the expression level of Survivin and VEGF proteins. Taken together, rAF-IL12 is a promising candidate for colon cancer therapy concerning its good profile in treating colon cancer-challenged mice as well as in the in vitro assays.